ANALISIS PENGARUH KOMUNIKASI, MOTIVASI, DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PT ARISAMANDIRI PRATAMA - haryani - (LPPM STIE DHARMAPUTRA SEMARANG, 2010)
This research aims to analyze how the influence of communications, motivation, and leadership to job satisfaction of employee at PT Arisamandiri Pratama, how the influence of job satisfaction, communications, motivation, and leadership to employee performance at PT Arisamandiri Pratama, and how the influence of communications, motivation, dan leadership to employee performance through job satisfaction of employee at PT Arisamandiri Pratama. Hypothesis that submitted in this research are (1) It is anticipated communications, mptivation, dan leadership influential positive to job satisfaction of employee at PT Arisamandiri Pratama, (2) It is anticipated job satisfaction, communications, motivatios, and leadership influential positive to employee performance at PT Arisamandiri Pratama, (3) It is anticipated communication, motivation, and leadreship influential positive to employee performance through job satisfaction of employee at PT Arisamandiri Pratama.Population in this research is employees at PT Arisamandiri Pratama which amounts to 1503. While sample in research amounts to 100. Data is obtained by primary data and secondary data. Data analysis done by using Path Analysis.Result of this research indicates that (1) communications, motivation, and leadership influential positive to job satisfaction of employee at PT Arisamandiri Pratama, thereby hypothesis 1,2, and 3 are received, (2) job satisfaction, communications, motivation, and leadership influential positive to employee performance at PT Arisamandiri Pratama, thereby hypothesis 4,5,6, and 7 are received, (3) communications, motivation, and leadership influential smaller positive to employee performance through job satisfaction of employee at PT Arisamandiri Pratama, thereby hypothesis 8,9, and 10 are refused. Keywords: communications, motivation, leadership, job satisfaction, employee performance.